PENGARUH KUALITAS VISUAL LANSKAP TERHADAP KUNJUNGAN WISATAWAN DESA WISATA PULESARI - Puji Lestari; Widodo Dwi Pramono, Retno (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
The management of landscape visual quality is an important aspect in attracting tourists, especially in tourism villages that rely on natural potential as their main attraction. The purpose of this study is to identify the influence of landscape visual elements on the level of tourist visits in Pulesari Tourism Village, Turi District, Sleman. The research employs a quantitative approach using multiple linear regression analysis, involving eight landscape visual elements such as color, lighting, vegetation, and water elements. The results show that color is the most significant element, with a regression coefficient of 1.725, while lighting has a smaller yet still relevant effect. The regression analysis also reveals that 56.3% of the variation in tourist visit levels can be explained by the visual quality elements of the landscape. The study concludes that landscape management focusing on visual harmony—such as attractive color combinations and well-managed vegetation—can enhance tourism appeal while supporting the sustainability of nature-based tourism. These findings provide practical recommendations for tourism village managers to optimize the landscape as a main attraction and improve the welfare of local communities.